Reduced activity of adenylyl cyclase 1 attenuates morphine induced hyperalgesia and inflammatory pain in mice - Johnson, Kayla; Doucette, Alexis; Edwards, Alexis; Verdi, Aleeya; McFarland, Ryan; Hulke, Shelby; Fowler, Amanda; Watts, Val J.; Klein, Amanda H. (Frontiers in Pharmacology, 2022)
Opioid tolerance and opioid-induced hyperalgesia during repeated opioid administration and chronic pain are associated with upregulation of adenylyl cyclase activity. The objective of this study was to test the hypothesis that a reduction in adenylyl cyclase 1 (AC1) activity or expression would attenuate morphine tolerance and hypersensitivity, and inflammatory pain using murine models. To investigate opioid tolerance and opioid-induced hyperalgesia, mice were subjected to twice daily treatments of saline or morphine using either a static (15 mg/kg, 5 days) or an escalating tolerance paradigm (10-40 mg/kg, 4 days). Systemic treatment with an AC1 inhibitor, ST03437 (2.5-10 mg/kg, IP), reduced morphine-induced hyperalgesia in mice. Lumbar intrathecal administration of a viral vector incorporating a short-hairpin RNA targeting Adcy1 reduced morphine-induced hypersensitivity compared to control mice. In contrast, acute morphine antinociception, along with baseline thermal paw withdrawal latencies, motor performance, exploration in an open field test, and burrowing behaviors were not affected by intrathecal Adcy1 knockdown. Knockdown of Adcy1 by intrathecal injection also decreased inflammatory mechanical hyperalgesia and increased burrowing and nesting activity after intraplantar administration of Complete Freund’s Adjuvant (CFA) one-week post-injection.